PENGESAHAN UNDANG-UNDANG KESEHATAN: KAJIAN REGULASI DAN TANTANGAN IMPLEMENTASI - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (Jurnal Kesehatan, 2025)
The enactment of the Health Law is a strategic step in the reform of the national health system with the aim of improving accessibility, quality, and efficiency of health services. This regulation includes new policies that prioritise the protection of patients' rights, the strengthening of health services, and the application of modern technology in health system management. However, studies indicate significant challenges in implementation, particularly related to human resources, funding, and harmonisation between the central and regional governments. Collaboration among stakeholders is key to addressing these issues. With appropriate implementation measures, the Health Law has the potential to bring about positive long-term changes in improving public welfare and achieving better national health outcomes.